2016
DOI: 10.1016/j.applthermaleng.2016.06.116
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of a radiatively cooled system for quantum optomechanical experiments in space

Abstract: The performance of a radiatively cooled instrument is investigated in the context of optomechanical quantum experiments, where the environment of a macroscopic particle in a quantumsuperposition has to be cooled to less than 20 K in deep space. A heat-transfer analysis between the components of the instrument as well as a transfer-function analysis on thermal oscillations induced by the spacecraft interior and by dissipative sources is performed. The thermal behaviour of the instrument in an orbit around a Lag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Detailed thermal studies of the MAQRO shield design showed the feasibility of achieving the temperature and vacuum technical requirements of MAQRO [37]. A more detailed thermal study showed even better results [38]. A collaboration of the University of Vienna, the University of Bremen and Airbus Defence &Space, successfully implemented a high-finesse, adhesively bonded optical cavity using space-proof glue and ultra-low-expansion (ULE) material [39].…”
Section: The Case For Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Detailed thermal studies of the MAQRO shield design showed the feasibility of achieving the temperature and vacuum technical requirements of MAQRO [37]. A more detailed thermal study showed even better results [38]. A collaboration of the University of Vienna, the University of Bremen and Airbus Defence &Space, successfully implemented a high-finesse, adhesively bonded optical cavity using space-proof glue and ultra-low-expansion (ULE) material [39].…”
Section: The Case For Spacementioning
confidence: 99%
“…These results could be further improved in a more detailed thermal analysis. In particular, this was achieved by using reflective instead of refractive optics [38] -yielding a temperature of T e ∼ 25 K for the optical bench and T e ∼ 12 K for the test volume.…”
Section: Thermal-shield Structurementioning
confidence: 99%
See 1 more Smart Citation
“…in space, where complicated cryogenic setups are not feasible [50]. In addition, thanks to the ultralow mechanical dissipation, it is possible to push boundaries of applications in ultrasensitive (e.g., force) detection [51][52][53], as has recently been demonstrated [54].…”
mentioning
confidence: 99%
“…The MAQRO mission proposes to do just this, as illustrated in Fig. 10b), though of course a satellite based experiment comes with a whole new set of experimental and financial challenges [125][126][127]. FIG.…”
Section: A Interferometrymentioning
confidence: 99%